A dual function of white coloration in a nocturnal spider Dolomedes raptor (Araneae: Pisauridae). (October 2015) - Lin, Tai-Shen; Zhang, Shichang; Liao, Chen-Pan; Hebets, Eileen A.; Tso, I-Min
Abstract : Nocturnal animals frequently possess seemingly conspicuous colour patterns that can function in a variety of ways (e.g. prey attraction, camouflage, predator avoidance, etc.). The use of colour patterns in intraspecific signalling, especially reproductive activities, in nocturnal animals has received relatively little attention. This study tested for a dual function of colour in the nocturnal fishing spider, Dolomedes raptor (Araneae: Pisauridae), whose males develop dimorphic white stripes at sexual maturation. We tested for a role in foraging as well as mate assessment. First, quantifications of the natural variation of male stripes indicated a correlation between stripe area and male body size and weight. Subsequent diet experiments confirmed that the area of a male's white stripes are body size-dependent and thus could potentially convey information to choosey females about male quality. Field experiments used dummies resembling D. raptor in appearance to test a prey attraction function of the white stripes. We found that dummies with the white stripes present attracted significantly more prey than those without stripes. Finally, we used males with manipulated phenotypes in laboratory mating trials and found that males with intact white stripes were significantly more likely to be accepted by females than those with the white stripes eliminated. Together, our results document a nutrient-dependent trait that functions not only in strengthening foraging success, but also in a mating context, increasing male mating success. We suggest that the role of these male white stripes in reproduction has been facilitated by their function in foraging. Highlights: Nocturnal fishing spiders can attract prey by their white body signals. The conspicuous signals also play roles in mate assessment at night. The brightness of the signals closely link with male condition. Sexual and natural selection favour this visual signal.